The language of translation in Brazil: written representations of oral discourse in Agatha Christie - Hanes, Vanessa Lopes Lourenço (2015)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão, Programa de Pós-Graduação em Estudos da Tradução, Florianópolis, 2015.